Socio-affective processing biases in severe alcohol use disorders: Experimental and therapeutic perspectives. (July 2020) - Pabst, Arthur; Heeren, Alexandre; Maurage, Pierre
Highlights: Preliminary data indicate that patients with SAUD exhibit biases toward social threat. Such biases may impede social relations and prognosis. We review current evidence and offer recommendations to directly study these biases. This new field could initiate innovative interventions reducing relapse in SAUD. Abstract: Previous literature has consistently reported socio-affective information processing impairments in patients with severe alcohol use disorder (SAUD). Some recent studies have also suggested that these patients might exhibit biases toward stimuli indicating social threat, such as angry or disgusted faces. Such biases have been largely documented in other psychopathological disorders like anxiety, where they play a critical role in the emergence and maintenance of the disorder. A comprehensive understanding of these biases in SAUD would thus deepen the understanding of interpersonal difficulties and relapse-related factors. However, to date, no study has directly explored these biases in SAUD. In order to initiate efforts to address this issue, we first review preliminary evidence supporting the hypothesis of biased processing of social threat in SAUD. Then, we identify possible pathways through which such biases might negatively impact the course of the disorder. Finally, we provide precise recommendations and available materials to develop research in this promising field, and underline the related theoretical and clinical perspectives.